All Days 2009
DOI: 10.2118/119661-ms
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Challenges in Northern Areas Due to Degradation of Wellbore Positioning Accuracy

Abstract: The surveyed position accuracy degrades when one approaches the magnetic and geographical poles. Both magnetic and gyroscopic tools are affected. We have analyzed the accuracy of several magnetic and gyroscopic services in a number of representative synthetic wellbores. Locations representative for the North Sea and the Barents Sea are chosen. The results show that an increase in horizontal target dimension by a factor of 2 is necessary when moving from 60°N to 75°N, to maintain the same hitting probability.Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In addition, some MWD gyroscope systems can be programmed to perform surveys from TD to surface when tripping out of hole and produce an overlapping data set that can be used for further quality-control improvement. It should be noted that the accuracy of any gyroscope system decreases with increasing geographical latitude, as described by Bang et al (2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some MWD gyroscope systems can be programmed to perform surveys from TD to surface when tripping out of hole and produce an overlapping data set that can be used for further quality-control improvement. It should be noted that the accuracy of any gyroscope system decreases with increasing geographical latitude, as described by Bang et al (2009).…”
Section: Discussionmentioning
confidence: 99%
“…The DSI affects b z and normally constitutes the major uncertainty in the reading. Bang et al (2009) evaluated the accuracy of both magnetic and gyroscopic directional surveys in northern areas and the effects of degraded azimuth accuracy upon wellbore design. They concluded that the lateral uncertainty increases by a factor of approximately two when moving from North Sea to Barents Sea latitudes and emphasized the need for optimized surveying programs and practices.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the earth's magnetic field as a reference for directional drilling has been described in several earlier papers (Zijsling and Wilson 1989;Russell et al 1995;Williamson et al 1998;Bang et al 2009). The geomagnetic reference field B is commonly described as a vector sum of the main field B m , the crustal field B c , and the disturbance field B d :…”
Section: The Earth's Magnetic Fieldmentioning
confidence: 99%
“…It is well known that the accuracy of the gyro is reduced the closer to the geographic North Pole (or South Pole) that the well is drilled as the earth's effects from rotation is less [1]. Similarly, the accuracy of magnetic directional measurements, all else being equal, is reduced the closer to the magnetic Poles a well is drilled as the horizontal field is smaller [2].…”
Section: Introductionmentioning
confidence: 99%